Energy harvesting systems : principles, modeling and applications - Kazmierski, Thomas J.; Beeby, Steve (New York : Springer, 2011)
Kinetic energy harvesting converts movement or vibrations into electrical energy, enables battery free operation of wireless sensors and autonomous devices and facilitates their placement in locations where replacing a battery is not feasible or attractive. This book provides an introduction to operating principles and design methods of modern kinetic energy harvesting systems and explains the implications of harvested power on autonomous electronic systems design. It describes power conditioning circuits that maximize available energy and electronic systems design strategies that minimize power consumption and enable operation. The principles discussed in the book will be supported by real case studies such as battery-less monitoring sensors at water waste processing plants, embedded battery-less sensors in automotive electronics and sensor-networks built with ultra-low power wireless nodes suitable for battery-less applications. -- Book Description.
1 Kinetic Energy Harvesting -- 2 Modelling, Performance Optimisation and Automated Design of Mixed-Technology Energy Harvester Systems -- 3 Simulation of Ultra-Low Power Sensor Networks -- 4 Remote Sensing of Car Tire Pressure.
Includes bibliographical references and index.
1
Keywords: Energy harvesting; Renewable energy sources; Energy conversion